Educational Needs in Premarital Counseling: Viewpoints of Couples Referring to Health Care Centers in Zanjan - pouran Mokhtari zanjani; parvin Shiri gheidari; saeedeh Mazloomzadeh; farzaneh zaheri; mahin roohani (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives: In recent years, premarital programs are considered to be important in order to promote the quality of married lives in our country. The aim of this study was to determine the pre-marital educational needs of couples referring to premarital education center of Zanjan. Materials and Methods: In a cross-sectional study, a self-administered questionnaire was used to collect data from 424 participants in pre-marriage counseling centers in zanjan, 2010. The questionnaire included demographic section and educational needs section that measured different subject of reproductive health, spousal relationships and Islamic rules and rights. Descriptive statistics, ANOVA and Kroscal Valiswere used for analyzing the data. Results: The need to education in all areas was higher than average in both groups. Comparing the scores showed no significant difference between males and females. The most important need in both groups was concerning the reproductive health. Conclusion: Regarding high education requirements in couples, it is necessary to modify the educational curriculums according to couples needs.